Humeral greater tuberosity osteolysis as a complication of intraosseous calcification migration: natural history depicted by imaging - Zampa, Virna; Aringhieri, Giacomo; Rossi, Piercarlo; Capanna, Rodolfo; Caramella, Davide (Acta Biomedica Atenei Parmensis, 2021)
Migration of calcification within the bone leading to greater tuberosity osteolysis is a peculiar complication of the calcifying tendinitis of the rotator cuff. The case of a 38-year-old woman complaining of right shoulder pain, which had been going on for one year, is hereby described. The evolution of the infraspinatus tendon calcifying tendinitis leading to osteolysis of the greater tuberosity of the humerus is depicted by imaging and, particularly, by the MR and CT features changing over time. In this paper we focus on the importance of both MR and CT exams in the diagnostic process of the different phases of the disease. The correlation between clinical symptoms and imaging features is also helpful for imaging interpretation: the most painful phase corresponds to the migration of the calcification, whereas pain tends to decrease when the osteolysis develops. Awareness of the existence of this condition may prevent unnecessary invasive procedures.